Measurement and numerical simulation of internal air flow in faculty of mechanical engineering admin office ventilation system - Mohd Amirul Husaini, Saat (2012)

(untitled)
Ventilation unit is critical for closed room such in Faculty of Mechanical administration office to recirculate air to entire room and maintain the surrounding temperature. Air is cycled to the inlet office space from inlet diffuser and outlet vent. However, the geometry position of the inlet diffuser and the furniture in the office effect the flow of the air cannot be supply directly to occupants. For this study, the objective is to investigate and observe the flow pattern in the office area due to obstruction by some partitions. A commercial CFD software was used which is ANSYS-Fluent to run the simulation. The real office dimension is 40 meters in length, 19 meters wide and 3 meters height. For the simulation RNG kε is used as the mathematical model for the flow in CFD. Results show that the obstruction occurred and effect the air distribution which is in agreement to previous researches. Analysis has been done after the simulation and the results show that the partitions in the office in good position which is the occupants are still in comfort while in working condition.